Forest Management and Operational Research: A Linear Programming Study - Wardle, P. A. (Management Science, 1965)
In this note the technique known as linear programming is applied to a problem of allocation which involves interaction between particular choices. Many management problems are further complicated by being dynamic—that is involving interaction through time as well as between variables—or they involve uncertainty. Such problems also lend themselves to numerical analysis. Through the description of an example it is hoped to demonstrate that the information available to management is both improved and extended by such analysis.